Korea's National Pension: Structural reform measures - Kang Koo Lee; Seung-Ryong Shin (Korea Development Institute (KDI), 2024)
South Korea has been under acute pressure to sustain its National Pension Plan without the risk of fund depletion. Given the looming fiscal threat, this study proposes the introduction of a new pension, a fully-funded system designed to ensure intergenerational equity. This reform aims to guarantee that future generations can receive pension benefits equivalent to the contributions paid and investment returns, without the fear of resource exhaustion. For contributions made prior to the reform, the benefits promised under the existing plan should be honored, while addressing the resultant financial shortfalls of the old pension through separate management and strategic utilization of the general budget to bridge these gaps. This study stresses the urgency of immediate action since the prompt implementation will substantially reduce fiscal stress.
Keywords: 330